2017
DOI: 10.3390/molecules22040610
|View full text |Cite
|
Sign up to set email alerts
|

The Pharmacological Effects of Lutein and Zeaxanthin on Visual Disorders and Cognition Diseases

Abstract: Lutein (L) and zeaxanthin (Z) are dietary carotenoids derived from dark green leafy vegetables, orange and yellow fruits that form the macular pigment of the human eyes. It was hypothesized that they protect against visual disorders and cognition diseases, such as age-related macular degeneration (AMD), age-related cataract (ARC), cognition diseases, ischemic/hypoxia induced retinopathy, light damage of the retina, retinitis pigmentosa, retinal detachment, uveitis and diabetic retinopathy. The mechanism by whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
61
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(63 citation statements)
references
References 171 publications
(227 reference statements)
0
61
0
2
Order By: Relevance
“…The natural lutein pigment has many excellent properties, such as the antioxidant properties possessed by most natural pigments. In addition, it also has great human health benefits like eye protection, prevention of various diseases, reduction of skin damage caused by UV, and so on [9][10][11]. Lutein detected in humans and animals is derived from plants, egg yolk, and processed foods containing lutein [12].…”
Section: Introductionmentioning
confidence: 99%
“…The natural lutein pigment has many excellent properties, such as the antioxidant properties possessed by most natural pigments. In addition, it also has great human health benefits like eye protection, prevention of various diseases, reduction of skin damage caused by UV, and so on [9][10][11]. Lutein detected in humans and animals is derived from plants, egg yolk, and processed foods containing lutein [12].…”
Section: Introductionmentioning
confidence: 99%
“…Lutein plays an important role as an antioxidant in the retina, thus protecting the eye from inflammation and oxidative stress (Eisenhauer, Natoli, Liew, & Flood, ; Jia et al, ). To date, most of the evidence regarding the protective role of lutein in eye health has been obtained in the context of age‐related macular degeneration (Liu et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that administration of lutein prevents high glucose‐induced oxidative stress and inhibits the onset of retinopathy in diabetic rats (Kowluru et al, ; Sasaki et al, ). Based on the ability of lutein to modulate retinal inflammation and oxidative stress (Eisenhauer et al, ; Jia et al, ; Kowluru et al, ; Liu et al, ; Sasaki et al, ), it is particularly important to determine whether this dietary carotenoid exerts anti‐aging effects, such as prevention of diabetes‐induced cellular senescence, in retinal cells.…”
Section: Introductionmentioning
confidence: 99%
“…This fact has been confirmed by the National Eye Institute (the USA) in the Age-Related Eye Disease Study (AREDS II), which aimed to study the efficacy of using lutein, zeaxanthin, and polyunsaturated fatty acids in ophthalmology. The mechanism by which lutein and zeaxanthin are involved in the prevention of dystrophic eye disorders can be associated with their physical blue light filtration properties and local antioxidant activity [13]. Our previous papers have shown that using lutein and zeaxanthin-containing drugs for AMD patients resulted in increased and stabled visual acuity and the improved functional activity of the visual system.…”
Section: Resultsmentioning
confidence: 99%